Prediabetes is an independent risk factor for sarcopenia in older men, but not in older women: the Bunkyo Health Study. Issue 6 (2nd September 2022) - Kaga, Hideyoshi; Tamura, Yoshifumi; Someya, Yuki; Naito, Hitoshi; Tabata, Hiroki; Kakehi, Saori; Yamasaki, Nozomu; Sato, Motonori; Kadowaki, Satoshi; Suzuki, Ruriko; Sugimoto, Daisuke; Kawamori, Ryuzo; et al.
Abstract: Background: Sarcopenia is a major cause of disability in the elderly. Although type 2 diabetes is a risk factor for increased sarcopenia, the relationship between prediabetes and sarcopenia has not been elucidated. We aimed to examine the relationship between sarcopenia and prediabetes. Methods: The design of this study is a cross‐sectional study. We evaluated glucose metabolism using the 75‐g oral glucose tolerance test and glycated haemoglobin, appendicular skeletal muscle mass, and hand grip strength in 1629 older adults living in an urban area of Tokyo, Japan. We investigated the frequency of sarcopenia in participants with normal glucose tolerance (NGT), prediabetes and diabetes. A multivariable logistic regression model was used to analyse the association between glucose tolerance and the prevalence of sarcopenia. Results: The mean age of participants was 73.1 ± 5.4 years. In men, 44.3% had NGT, 26.6% had prediabetes, and 29.1% had diabetes. In women, the distribution was 56.1%, 28.8% and 15.2%. The prevalence of sarcopenia was 12.7% in men and 11.9% in women. Logistic regression revealed that prediabetes and diabetes are independent risk factors for sarcopenia in men (prediabetes, odds ratio [OR] = 2.081 [95% confidence interval CI: 1.031–4.199]; diabetes, OR = 2.614 [95% CI: 1.362–5.018]) and diabetes, but not prediabetes, is an independent risk factor for sarcopenia in women (prediabetes, OR = 1.036 [95% CI: 0.611–1.757]; diabetes, OR = 2.099 [95% CI: 1.146–3.844]). In both sexes, higher age (men, OR = 1.086 [95% CI: 1.028–1.146]; women, OR = 1.195 [95% CI: 1.142–1.251]), higher body fat percentage (men, OR = 1.346 [95% CI: 1.240–1.461]; women, OR = 1.218 [95% CI: 1.138–1.303]) and lower body mass index (men, OR = 0.371 [95% CI: 0.299–0.461]; women, OR = 0.498 [95% CI: 0.419–0.593]) were independent risk factors for sarcopenia. Conclusions: Although we confirmed that diabetes mellitus is associated with sarcopenia in both sexes, prediabetes is associated with sarcopenia in men, but not in women.